REHABILITASI ESTETIK DAN FUNGSI KUNYAH DENGAN PERAWATAN COMPLEX BRIDGE - Rahardyan Parnaadji (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
Complex bridge is a fixed denture that replaces missing teeth with the activities of different functions. Complex bridge design can use porcelain fused to metal restorations that combines the power, accuracy and appropriateness of the placement with the aesthetic effect of ceramic crowns. This design can improve aesthetic and mastication functions. The aim of this case report paper was to explain the management of treatment of a complex bridge could improve an aesthetic and mastication functions on case of improving teeth restoration. The case study was carried out on a 23 year old male patient. He hasn’t self confidence because he had teeth with old restoration an missing teeth in posterior. He needed fixed denture to improve his aesthetic and functional performance. A complex bridge were designed to improving teeth and replace the posterior maxillary teeth in 15, 14, 13, 12, 11, 21, 23, 24, 25. In conclusion, the complex bridge is superior treatment can improve aesthetic and functional performance .